2023
DOI: 10.3390/ijms241512264
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of H2S-ABA Crosstalk in Maize Thermotolerance through the ROS-Scavenging System

Jia-Qi Wang,
Ru-Hua Xiang,
Zhong-Guang Li

Abstract: Hydrogen sulfide (H2S) and abscisic acid (ABA), as a signaling molecule and stress hormone, their crosstalk-induced thermotolerance in maize seedlings and its underlying mechanism were elusive. In this paper, H2S and ABA crosstalk as well as the underlying mechanism of crosstalk-induced thermotolerance in maize seedlings were investigated. The data show that endogenous levels of H2S and ABA in maize seedlings could be mutually induced by regulating their metabolic enzyme activity and gene expression under non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…In recent years, substantial studies have reported that H 2 S as a signaling molecule modulates seed germination, stomatal movement, floral induction, organ senescence, and plant stress response [ 2 , 4 , 5 , 6 ]. Our studies also found that as a signaling molecule, H 2 S was able to increase maize thermotolerance, which is implicated in the signaling crosstalk of H 2 S with calcium, nitric oxide, methylglyocal, and abscisic acid [ 2 , 7 , 8 ]. However, whether H 2 S-promoted maize thermotolerance is related to sucrose signaling remains unclear.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…In recent years, substantial studies have reported that H 2 S as a signaling molecule modulates seed germination, stomatal movement, floral induction, organ senescence, and plant stress response [ 2 , 4 , 5 , 6 ]. Our studies also found that as a signaling molecule, H 2 S was able to increase maize thermotolerance, which is implicated in the signaling crosstalk of H 2 S with calcium, nitric oxide, methylglyocal, and abscisic acid [ 2 , 7 , 8 ]. However, whether H 2 S-promoted maize thermotolerance is related to sucrose signaling remains unclear.…”
Section: Introductionmentioning
confidence: 72%
“…In plants, H 2 S and SUC are key signaling molecules which regulate many kinds of stress responses, including heat stress [ 2 , 6 , 7 , 29 ]. However, whether crosstalk of H 2 S and SUC signaling exists in the formation of maize thermotolerance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, HS can result in oxidative damage due to the excessive accumulation of reactive oxygen species (ROS) [ 11 ]. The level of ROS within plant cells is strictly controlled by the ROS scavenging system to maintain ROS homeostasis which has been found to be positively correlated with maize thermotolerance [ 12 ]. In addition, heat shock proteins (HSPs), known as molecular chaperones, participate in a wide range of biological processes including HS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%